Some New Explicit Values of Parameters λn and μn of Quotients of Eta-Function. (18th February 2013) - Saikia, Nipen
Abstract : We find some new explicit values of the parametersλ n andμ n of quotients of eta-function by using Ramanujan's class invariants.